L’espace du militantisme LGBT à l’épreuve des présidentielles - Massimo Prearo (Genre, Sexualité et Société)
The presidential campaign of 2012 was an moment of unprecedented professionalization and structuration in the mobilization of lesbians, gays, bisexuals and trans persons (LGBT), and one of very high visibility for the « LGBT movement ». The strategic use of certain activist references, that symbolically call for an inter-associative LGBT movement that is both united and plural, resulted in a discourse that the candidates had to reformulate in order to adopt the and perform the discourse during their public remarks at the general Meeting for Equality organized by the associations. This article analyzes the dynamics at play in the space of LGBT activism, and, more widely, the cleavages structuring the political field that were revealed during the presidential election of 2012. It is observed that the logics of LGBT movement institutionalization and those of activist priorities result in competition between politics and inter-associative networks.